Reading between the lines: the experiences of taking part in a community reading project. Issue 2 (30th November 2007) - Hodge, S; Robinson, J; Davis, P
Abstract : Despite the popularity of reading groups, and the increased number of general-practitioner-referred bibliotherapy schemes in the UK, there has been relatively little research on the effects of reading works of literature on the well-being and health of readers. This paper reports the findings of a study set up to explore people's experiences of taking part in community reading groups run by the Get into Reading Project in Wirral, Merseyside, UK. A qualitative approach was adopted, using three methods. These were participant observation with five reading groups, a key stakeholder interview and, with a sixth group, a single case study that consisted of observation and interviews with group members. The fieldwork conducted with the six groups took place in a variety of settings, including libraries, a residential drug rehabilitation unit and a hostel for homeless men. The research participants were all over 18 years of age, and all were members or facilitators of Get into Reading reading groups. The data were analysed thematically using NVivo qualitative analysis software. The findings show that the groups do not have a specific, targeted, therapeutic function, their primary purpose being more broadly literary, with literature itself trusted both to serve a coalescing social purpose and to offer non-specified but individual therapeutic benefits. Further work should be undertaken to explore the social and therapeutic benefits of reading literature in community settings.